Dinamika Politik dan Pemerintahan Venezuela di Bawah Kepemimpinan Presiden Nicolas Maduro - Kunkunrat Kunkunrat; Ade Priangani; Astrid Aulia Monica (TRANSBORDERS: International Relations Journal, 2021)
Venezuela is one of the Latin American countries that have a history of governance dynamics quite complex, ranging from coup attempts, dictatorial leadership to economic and social problems. In this study discussed the dynamics of politics and economics under the leadership of Nicolas Maduro and the policy steps taken in overcoming the problem of the economic crisis which led to the instability of the country. In this study using descriptive research methods and library research data collection techniques, and using the theory of decision-making process by Graham T. Allison to analyze the results of the study. In conclusion, Maduro's leadership tends to use organizational process models or decisions based on the work of the organization/party in determining the direction of policy, both domestic and foreign policy. This was due to the strong influence of Maduro supporters from the United Socialist Party of Venezuela (PSUV) party, where the party was a supporter of the previous president, Hugo Chavez. Although Maduro inherited the Chavez leadership style that embraced the socialist system, Maduro was deemed unsuccessful in overcoming the problem of the Venezuelan crisis.